The clinical practice of drug information - Gabay, Michael (Burlington, MA : Jones & Bartlett Learning, 2016)
'This resource will educate students and pharmacists on traditional drug information topics while providing an extensive background on more recent practice areas. This is a user-friendly text with multiple examples that can be used in education and training, as well as clinical practice. Each chapter includes learning objectives, key terms, examples and cases, and review questions'--
Introduction to drug information practice -- The systematic approach to responding to drug information requests -- Tertiary sources of information -- Secondary sources of information -- Primary sources of information -- Introduction to clinical study design -- Research study design -- Descriptive statistics -- Inferential statistics -- Epidemiology and measures of associated risk -- Correlation and regression -- Analysis and interpretation of noninferiority trials -- Errors related to clinical research -- Evidence-based medicine -- How to prepare an effective journal club -- Medication safety -- Medication use policy and performance assessment -- Formulary management -- Academic detailing and industry relationships -- Medical writing and peer review -- Informatics and clinical decision support -- Basic principles of pharmacoeconomics.
This book includes online access at www.jblearning.com, please refer library staff for the password.
Includes bibliographical references and index.
Keywords: Drug Information Services; Pharmaceutical Services